ANALISIS FAKTOR PENGETAHUAN, REPUTASI, LINGKUNGAN, DAN RELIGIUSITAS TERHADAP MINAT MENABUNG PADA SISWA SMK JURUSAN PERBANKAN SYARIAH - Salsabilla, Ashifa Isnaeni; Sulasih, Sulasih; Parno, Parno; Setianingsih, Dias (Indonesian Scientific Journal of Islamic Finance, 2025)
Although Indonesia has a predominantly Muslim population, the market share of Islamic banking in 2020 remained relatively modest at only 6.18%. One of the major challenges lies in the low savings interest among the younger generation. Previous studies have investigated the influence of knowledge, reputation, environment, and religiosity on saving behavior; however, the findings remain inconclusive, thereby creating a research gap that merits further exploration. The novelty of this study lies in its simultaneous examination of these four variables within the context of vocational high school students majoring in Sharia banking who have direct access to a school-based mini-bank facility, an environment that has rarely been addressed in prior research. Employing a quantitative approach, the study utilized a survey method with purposive sampling involving 139 students from SMK Negeri 1 Purwokerto. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression, preceded by validity, reliability, and classical assumption tests. The findings reveal that knowledge exerts a significant negative effect on saving interest, while reputation, environment, and religiosity demonstrate significant positive effects. Collectively, these four variables significantly influence saving interest, with a coefficient of determination of 40.2%. This study highlights that Islamic banks may enhance their attractiveness to young customers by strengthening institutional reputation, fostering supportive environments, and reinforcing religious values. Nevertheless, positive perceptions of products and services should be complemented by improved financial knowledge to further optimize savings interest in Islamic banking